Energy Level Alignment at Bebq2/PEI/ITO Interfaces Studied by UV Photoemission Spectroscopy. (31st January 2017) - Shimizu, Kohei; Fukagawa, Hirohiko; Morii, Katsuyuki; Kinjo, Hiroumi; Sato, Tomoya; Ishii, Hisao
ABSTRACT: A polyethyleneimine (PEI) interlayer has been applied on indium tin oxide (ITO) to improve electron injection in organic devices including inverted organic light-emitting diodes (OLEDs). To understand the improvement effect by PEI insertion, the energy level alignment at bis(10-hydroxybenzo[h]quinolinato)beryllium (Bebq2 )/PEI/ITO interfaces was investigated by UV photoemission spectroscopy (UPS). The deposition of a PEI layer was found to reduce the absolute work function of ITO by 1.4 eV. The vacuum level shifts at Bebq2 /ITO and Bebq2 /PEI interfaces were also determined as 0.3 eV and 0.1 eV in the direction to reduce the electron injection barrier, respectively. Thus the work function reduction by PEI and downward vacuum level shift at the Bebq2 /PEI interface can contribute to the improvement effect. Kelvin probe measurement revealed the weak orientation polarization in Bebq2 film with the bottom side positively polarized. This polarization polarity is also advantageous for electron injection in inverted devices.